Pyrazolylazophenyl Ether‐Based Photoswitches: Facile Synthesis, (Near‐)Quantitative Photoconversion, Long Thermal Half‐Life, Easy Functionalization, and Versatile Applications in Light‐Responsive Systems. Issue 58 (13th September 2019) - Zhang, Zhao‐Yang; He, Yixin; Zhou, Ying; Yu, Chunyang; Han, Lu; Li, Tao
Abstract: Molecular photoswitches (e.g., azobenzenes) can reversibly interconvert between their thermodynamically stable and metastable isomers upon light irradiations. However, it remains challenging to integrate both high bidirectional photoconversion and long metastable‐state lifetime into a photoswitchable functionality. Here, we introduce pyrazolylazophenyl ethers (pzAzo ethers ) as a class of azo photoswitches that provides quantitative (>98 %) trans – cis photoisomerization (365 nm light), near‐quantitative (95–96 %) reverse isomerization (532 nm light), and a long cis ‐isomer half‐life of three months. They can be easily synthesized in high yields and readily functionalized at one or both sides with a broad scope of substituent groups. Molecular systems incorporating pzAzo ethers can be endowed with high responsiveness, robust reversibility, and long persistent metastable states. Such superior yet pragmatic azo switches hold high promise for upgraded photoregulation in many light‐responsive applications. Abstract : Great switches : Pyrazolylazophenyl ether‐based photoswitches integrate (near‐)quantitative photoisomerizations and a three‐months thermal half‐life, and they can be easily prepared and functionalized for incorporation into various chemical systems (see figure, PSS=photostationary state).